1999
DOI: 10.1038/sj.onc.1202905
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of ING1 expression in sporadic breast cancer

Abstract: Down regulation of the ING1 candidate tumour suppressor promotes growth in soft agar and focus formation in vitro and tumour formation in vivo. ING1 encodes a nuclear, cell cycle-regulated protein, overexpression of which e ciently blocks cell growth and is capable of inducing apoptosis in di erent experimental systems. Here we present the ®rst report of ING1 mutation and expression analysis in a total of 452 cancer samples. One germline missense alteration and three germline silent alterations were detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 22 publications
4
87
0
Order By: Relevance
“…Ing1 levels are also increased upon the induction of apoptosis in P19 cells by serum deprivation, and overexpression of Ing1 in P19 and rodent fibroblasts enhances Myc-dependent apoptosis (28). Evidence indicates that expression of Ing1 is repressed in a majority of breast and lymphoid cancer cell lines and glioblastomas and is mutated in some neuroblastoma cell lines, breast cancers, and brain tumors (21,52,74). Together, these observations suggest that Ing1 acts as a tumor suppressor and that it is involved in regulating apoptosis.…”
mentioning
confidence: 68%
“…Ing1 levels are also increased upon the induction of apoptosis in P19 cells by serum deprivation, and overexpression of Ing1 in P19 and rodent fibroblasts enhances Myc-dependent apoptosis (28). Evidence indicates that expression of Ing1 is repressed in a majority of breast and lymphoid cancer cell lines and glioblastomas and is mutated in some neuroblastoma cell lines, breast cancers, and brain tumors (21,52,74). Together, these observations suggest that Ing1 acts as a tumor suppressor and that it is involved in regulating apoptosis.…”
mentioning
confidence: 68%
“…Although the reason for reduced ING2 expression in human melanomas is unclear, we cannot rule out mutation of the ING2 gene in melanoma because different tumour type may have different mechanisms for gene inactivation. For example, reduced ING1 expression was found in 73% of non-small cell lung cancer biopsies (Kameyama et al, 2003) and 44% of breast cancer primaries (Toyama et al, 1999), while no missense mutation were found in these lung cancer biopsies and only one missense mutation was found in 377 breast cancer carcinomas (0.27%). On the other hand, reduced nuclear ING1 expression was associated with a much higher mutation rate (20%) of the ING1 gene in human primary melanomas .…”
Section: Discussionmentioning
confidence: 99%
“…p33 cDNA in T.Tn cells was ampli®ed by RT ± PCR using the total RNA fraction according to the method of Toyama et al (1999). Thereafter, direct sequencing of the products showed that there was no alteration in p33 sequence (data not shown).…”
Section: Transfection With P33mentioning
confidence: 99%
“…Overexpression of p33 inhibits cell cycle progression from G 0 /G 1 to S phase (Garkavtsev et al, 1996), and decreased p33 expression was observed in breast cancers (Toyama et al, 1999;Tokunaga et al, 2000), gastric cancers (Oki et al, 1999), lymphoid tumor cell lines (Ohmori et al, 1999) and esophageal squamous cell cancers (ESCC) (Chen et al, 2001). Tumor-speci®c mutations were detected in the p33 gene in head and neck squamous cell carcinomas (Gunduz et al, 2000) and ESCC (Chen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%